ANALYSIS OF THE MAJOR ECONOMIC FACTORS OF THE WIND TURBINES PERFORMANCE BASED ON THE RESULTS OF COMMERCIAL SERVICE EXPERIENCE OF THE WIND-FARMS IN LATVIA - Y. A. Rolik; A. V. Gornostay (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The article examines the main aspects of commercial realization of wind-power projects as application part of wind-power industry with the view of evaluating viability and financial feasibility of the specified projects. The paper presents the results of 10 years’ commercial service experience of two wind-farms accomplished on the basis of three wind turbines (WT) – NORDEX N54, 1.0 MW capacity each, 60 m tower height, located in settlements Uzava and Alsunga on the coast of the Baltic Sea in the Republic of Latvia. The results were obtained by the way of collation of the site-location wind conditions and the major economic factors of the WT operation in the considered wind farms. The collation included the following estimated figures: annual electricity production, average annual income received during the period under review, electricity prime cost. The WT-site location wind conditions and the site-distance from the coastal line have an effect on the WT-performance economic factors that provide an integral insight into the viability and financial feasibility of the wind energy projects.Based on the analysis of the obtained data, the authors show that the relative produced energy value decreases 10 % with each kilometer wind-farm site distance from the coastal line of the Baltic Sea. They also indicate the effect the surrounding-area wind conditions and the TW-location site remoteness from the costal line have on the prime cost of the electricity generated by the wind farms. There is a good reason to utilize the presented results in the future for the wind-energy potential valuation of a particular region and a wind-farm location choice as well as for making particular managerial decisions in the way of realizing commercial wind-energy projects.